(untitled) (Jurnal Bahasa Lingua Scientia, 2012)
This paper is intended to give a brief overview of the potential benefits of Information and Communication Technology (ICT) use in education and the ways by which different ICTs have been used in education thus far. An example of making use Internet resources for teaching English for young learners is also performed in this paper. Then this paper concludes with an expectation of future ICT-based education in Indonesia.